Visible-light-promoted syntheses of β-keto sulfones from alkynes and sulfonylhydrazides. Issue 18 (22nd April 2016) - Cai, Shunyou; Chen, Danling; Xu, Yaohui; Weng, Wen; Li, Lihuang; Zhang, Ruijie; Huang, Mingqiang
Abstract : Functionalized β-keto sulfones were prepared under the synergistic interactions of visible light irradiation, Ru(bpy)3 Cl2, oxygen, KI, and NaOAc basic additive. Abstract : A variety of functionalized β-keto sulfones were smoothly prepared through oxysulfonylation of commercially available alkynes with sulfonylhydrazides under the synergistic interactions of visible light irradiation, Ru(bpy)3 Cl2 photocatalyst, oxygen, KI, and NaOAc basic additive under very mild reaction conditions.